Development Of Portable Air Conditioning Using Peltier Effect For Small Area Uses - Ab Hadi, Nik Azran; A. Subki, A. Shamsul Rahimi; Abd Rashid, Wan Norhisyam; Jidin, Aiman Zakwan; Tan, Sze Ying (Penerbit Universiti,UTeM, 2018)
Air conditioning is the science of controlling dependent parameters such as human comfort,temperature,relative humidity and air quality.This paper presented the development of a portable air conditioning using Peltier Effect in the small area uses using Boost converter as current control devices.A Boost converter has been designed in order to supply a sufficient current that required to the Peltier module to operate.An Arduino UNO board is used to supply the boost converter with pulse width modulation to ensure the boost converter is able to boost the current up until required range of operation. The circuit then simulated using Proteus PCB Design and Simulation to validate the output voltage and current. Based on our findings,the boost converter is operated as predicted in term of a step up the current and voltage. The temperature for cold side are observed reach 23.6 °C in 300s at less than 1A current.This is due to Peltier module is a current control device where when the current increases,the efficiency decreases while maximum cooling occurs at some specific current.If we increased the output current,the cold side is observed to reach 23.6 °C in less than 240s.Based on our findings,this portable air conditioning is useful to cool a small area (20inch x 20inch) with ambient temperature during full load is consistently recorded at 23.6°C.